2013
DOI: 10.1177/1040638712470448
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Bovine herpesvirus 1 infections in neonatal dairy calves

Abstract: Abstract. During a 6-year period, 62 out of 2,980 calves examined (2.08%) between 1-30 days of age had lesions consistent with Bovine herpesvirus 1 infection. The mean and median age of affected calves was 14 days of age. Most cases of infection were in calves 12 and 15 days of age, with 34 calves (54.8%) affected; 14 calves (22.6%) were between 16-21 days of age; 11 calves (17.8%) were between 7-11 days of age; and 3 calves (4.8%) were between 22-30 days of age. In 29 of the calves, the adrenal gland was the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Moreover, the type of abomasal damage caused by parasites, referred to as nodules, is quite different from that described most commonly in veal calves (Table 4). Finally, although some viruses can cause lesions in several organs (including the abomasum) in dairy calves (Moeller et al, 2013), beef calves (Bianchi et al, 2017), and adult cattle (Assis et al, 2002), the prevalence of viral diseases is much lower than the prevalence of abomasal damage (2% compared with >70%; Brscic et al, 2011;Bianchi et al, 2017). Viruses, although possibly causing some of the cases of abomasal damage found in veal calves (Table 5), are unlikely to be a main factor in the majority of damage found.…”
Section: Microorganismsmentioning
confidence: 97%
See 1 more Smart Citation
“…Moreover, the type of abomasal damage caused by parasites, referred to as nodules, is quite different from that described most commonly in veal calves (Table 4). Finally, although some viruses can cause lesions in several organs (including the abomasum) in dairy calves (Moeller et al, 2013), beef calves (Bianchi et al, 2017), and adult cattle (Assis et al, 2002), the prevalence of viral diseases is much lower than the prevalence of abomasal damage (2% compared with >70%; Brscic et al, 2011;Bianchi et al, 2017). Viruses, although possibly causing some of the cases of abomasal damage found in veal calves (Table 5), are unlikely to be a main factor in the majority of damage found.…”
Section: Microorganismsmentioning
confidence: 97%
“…Infections caused by fungi, bacteria, parasites, and diseases caused by viruses are hypothesized to lead to the development of abomasal damage in calves (Ross, 1963;Smith, 1966;Stokka and Perino, 2000;Marshall, 2009;Moeller et al, 2013); see Tables 2, 3, 4, and 5 for an overview of these studies. This hypothesis is partly because microorganisms are known to cause peptic ulcers in humans (Overmier and Murison, 2013).…”
Section: Microorganismsmentioning
confidence: 99%
“…Raaperi et al (2012a) highlighted that herds with a BoHV-1 within-herd seroprevalence of between 1 and 49%, have a higher risk of abortion (odds ratio = 7.3). Moeller et al (2013) reported that 2% of calves submitted for necropsy to the California Animal Health and Food Safety Laboratory (Tulare, CA) over a 6-yr period had lesions consistent with systemic BoHV-1 infection.…”
Section: Introductionmentioning
confidence: 99%
“…6). 2,56,59,60,67 Not addressed in Kennedy's article, but pertinent to some outbreaks of BoHV-1 abortion, are obstetrical complications such as secondary bacterial metritis affecting individual dams that abort in late gestation. 50,66,76,99 A series of articles in the 1980s by Dr Janice Miller and colleagues at the National Animal Disease Center at Ames, Iowa, added greatly to our understanding of the reproductive effects of BoHV-1, including those in nonpregnant cattle.…”
Section: The Kennedy Articlementioning
confidence: 99%